2016
DOI: 10.1088/1475-7516/2016/08/071
|View full text |Cite
|
Sign up to set email alerts
|

The impact of baryons on the direct detection of dark matter

Abstract: The spatial and velocity distributions of dark matter particles in the Milky Way Halo affect the signals expected to be observed in searches for dark matter. Results from direct detection experiments are often analyzed assuming a simple isothermal distribution of dark matter, the Standard Halo Model (SHM). Yet there has been skepticism regarding the validity of this simple model due to the complicated gravitational collapse and merger history of actual galaxies. In this paper we compare the SHM to the results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 97 publications
6
94
0
Order By: Relevance
“…In the case of annihilating DM, the effect of including baryons is more pronounced; DM-only halos are less spherical/more elongated than those including baryons. This effect has been previously studied and our results are consistent with previous analyses [13,19,24,[59][60][61][62][63][64].…”
Section: Observed Axis Ratiosupporting
confidence: 93%
“…In the case of annihilating DM, the effect of including baryons is more pronounced; DM-only halos are less spherical/more elongated than those including baryons. This effect has been previously studied and our results are consistent with previous analyses [13,19,24,[59][60][61][62][63][64].…”
Section: Observed Axis Ratiosupporting
confidence: 93%
“…[66,67] found that a Maxwellian speed distribution is a good fit to the speed distribution in their hydrodynamical simulations. This may be because adiabatic contraction makes the logarithmic slope of the density profile in the Solar neighbourhood closer to that of an isothermal sphere [67]. Even though the Maxwellian speed distribution is a good fit, there is still significant halo to halo variation in the peak speed/velocity dispersion.…”
Section: B Hydrodynamicalmentioning
confidence: 97%
“…Borzognia et al [66] selected galaxies from the EAGLE [69] and APOSTLE [70] projects with masses in the range (10 12 − 10 13 M ⊙ ) that satisfied observational constraints on the MW rotation curve and stellar mass. Kelso et al [67] [68] studied four MW-like galaxies, with masses in the range 0.7 − 0.9 × 10 12 M ⊙ with a variety of different merger histories (i.e. quiescent or with one or more relatively recent major mergers).…”
Section: B Hydrodynamicalmentioning
confidence: 99%
“…Nevertheless it is well known from simulations that the SHM is not a good description of a Milky Waylike halo. There have been numerous attempts to find empirical fitting functions to better capture the phase space structure found in N-body and hydrodynamic simulations [26,[67][68][69][70][71] as well as parameterisations that decompose the speed or velocity distribution in an astrophysics independent way [72,73]. Some studies of data from hydrodynamic simulations suggest that the standard halo model is a satisfactory approximation to the Milky Way once baryons are taken into account (e.g., Ref.…”
Section: Speed Distributionmentioning
confidence: 99%
“…Some studies of data from hydrodynamic simulations suggest that the standard halo model is a satisfactory approximation to the Milky Way once baryons are taken into account (e.g., Ref. [70]), however others such as Sloane et al [71] claim that the SHM overpredicts the amount of dark matter in the tail and hence gives overly optimistic discovery limits. To address these concerns, and because when discriminating between WIMPs and neutrinos the high speed tail of the distribution is especially important, we show discovery limits for a range of different models.…”
Section: Speed Distributionmentioning
confidence: 99%